Analisis Perbandingan Tingkat Kesejahteraan Pedagang Sayuran di Daerah Pariwisata dan di Daerah Pertanian - SALSABILA, ALLYA RIZKA; DEWI, RATNA KOMALA; ARISENA, GEDE MEKSE KORRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Analysis of Comparative Welfare Level of Vegetable Traders in Tourism Areas and Agricultural Areas. The field of trade supports the economy not only through the tourism sector but also through the agricultural sector. The daily demand for vegetables makes the sales of this commodity very promising. However, the perishable nature of vegetables prevents them from being sold for more than a day. This research aims to determine the income of vegetable traders and to compare the welfare levels of traders in tourist areas and agricultural areas. The study was conducted on all vegetable traders at Kuta 1 Market as a representative of the tourist area, and Blahkiuh Traditional Market as a representative of the agricultural area, using qualitative and quantitative analysis methods. The research results show that the monthly income of vegetable traders at Kuta 1 Market is Rp5.986.724, which is higher compared to Rp5.211.699 at Blahkiuh Traditional Market. The comparison of the welfare levels of traders in tourist and agricultural areas, tested using the Mann Whitney test, shows an Asymp. Sig. value of 0,616, indicating that the welfare levels of vegetable traders do not significantly differ. The advice given to vegetable traders is to keep records of their transactions, including income and expenses, and for the government to pay more attention to the welfare issues of traders, especially those in the vegetable sector, to ensure that no traders experience low levels of welfare in the future.